ANALISIS KESALAHAN FAKTA DAN KESALAHAN KONSEP MAHASISWA DALAM MENYELESAIKAN SOAL GEOMETRI ANALITIK RUANG - Syamsuddin Mas'ud (Didaktika : Jurnal Kependidikan, 2020)
This study aims to describe both fact and concept error of students in solving space analytic geometry problems. The subjects of this research are two students of Mathematics Department of Universitas Negeri Makassar. Each of them represents for each error (fact and concept errors). The collecting data were employed by using space analytic geometric tests and depth-interview. Interview guidelines and researcher were as research instruments. Data were qualitatively analyzed, using three stages of analysis: data reduction, data display and concluding. The main findings of this research are (1) the subject of fact error made mistakes in writing vector symbols, (2) the subjects of concept error made mistakes in identifying an equation (plane equation or line equation), since his focus was only in the number of variables of the equation.Keywords: fact error, concept error, space analytic geometry